Reação de cultivares e acessos de melancia ao parasitismo de Rotylenchulus reniformis e Meloidogyne javanica - Lima, Grace Kelly Leite de (2008)
The objective of this work was to evaluate the reaction of watermelon cultivars and accessions to the parasitism of Rotylenchulus reniformis and Meloidogyne javanica, in two experiments carried out at a greenhouse of the Departmento de Ciências Vegetais of the Universidade Federal Rural do Semi-Árido (UFERSA), in a completely randomized design with nineteen treatments and five replications, being the experimental unity constituted of a seedling per pot. In the first experiment, it has been studied the resistance of six commercial cultivars ( Sugar Baby , Blowing , Crimson Sweet , Charleston Gray , Omaru Yamato and Mickylee ) and thirteen accessions ( M-03 , M-08 , M-10 , M-14 , M-16 , M-17 , M-18 , M-19 , UP-02 , UP-04 , UP-10 , UP-12 and UP-18 ) of watermelon collected in the Mossoró and Upanema counties to the parasitism of Rotylenchulus reniformis. It was used the melon cultivar AF 646 as the control for the feasibility of the inoculum. The soil of each experimental unit was infested with 2,000 vermiformes forms of R. Reniformis (males, immature adult females and juveniles) and at 51 days after the infestation, it was evaluated to the following variables: number of nematodes into the soil, number of nematodes into the roots, total number of nematodes and reproduction factor. The cultivars Blowing and Charleston Gray , and the accession M-16 behaved themselves as nonefficient host to the population of R. reniformis. The cultivars Sugar Baby , Crimson Sweet , Omaru Yamato and Mickylee, and the accessions M-03 , M-08 , M-10 , M-14 , M-17 , M-18 , M-19 , UP-02 , UP-04 , UP-10 , UP-12 and UP-18 behaved as poor host to the population of R. reniformis. In the second experiment was tested the resistance of four commercial cultivars ( Sugar Baby , Crimson Sweet , Charleston Gray and Mickylee ) and fifteen accessions ( M-03 , M-04 , M-08 , M-10 , M-14 , M-16 , M-17 , M-18 , M-19 , UP-02 , UP-04 , UP-05 , UP-10 , UP-12 and UP-18 ) of watermelon collected also in the Mossoró and Upanema counties to the parasitism of M. javanica. It was used the tomato cultivar Santa Cruz Kada Gigante as the control for the feasibility of the inoculum. The soil of each experimental unit was infested with 5,000 eggs of M. Javanica and at 52 days after the infestation, it was evaluated to the following variables: root-gall and eggs- mass indexes and listed the ways of development of M. Javanica observed into the root system. The cultivars Sugar Baby , Crimson Sweet , Charleston Gray and Mickylee , and the accessions M-03 , M-04 , M-08 , M-10 , M-14 , M-16 , M-17 , M-18 , M-19 , UP-02 , UP-04 , UP-05 , UP-10 , UP-12 and UP-18 were susceptible to M. Javanica in terms of root-gall index